2015
DOI: 10.1038/srep14404
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Increases Sensitivity of Pancreatic Cancer Cells to Gemcitabine by Reducing CD133+ Cell Populations and Suppressing ERK/P70S6K Signaling

Abstract: The prognosis of pancreatic cancer remains dismal, with little advance in chemotherapy because of its high frequency of chemoresistance. Metformin is widely used to treat type II diabetes, and was shown recently to inhibit pancreatic cancer stem cell proliferation. In the present study, we investigated the role of metformin in chemoresistance of pancreatic cancer cells to gemcitabine, and its possible cellular and molecular mechanisms. Metformin increases sensitivity of pancreatic cancer cells to gemcitabine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 52 publications
2
37
0
2
Order By: Relevance
“…In line with these findings, the administration of anti-CD44 monoclonal antibody to a human PC xenograft mouse model increased Gemcitabine sensitivity[120]. Additionally, Metformin enhanced the capacity of Gemcitabine to inhibit the proliferation of PC cells by inhibiting the proliferation of CD133 + cells[121]. Side population PCSC identified by Van der Broeck in 2012[111] are resistant to Gemcitabine.…”
Section: Pancreatic Cancer Stem Cellsmentioning
confidence: 96%
“…In line with these findings, the administration of anti-CD44 monoclonal antibody to a human PC xenograft mouse model increased Gemcitabine sensitivity[120]. Additionally, Metformin enhanced the capacity of Gemcitabine to inhibit the proliferation of PC cells by inhibiting the proliferation of CD133 + cells[121]. Side population PCSC identified by Van der Broeck in 2012[111] are resistant to Gemcitabine.…”
Section: Pancreatic Cancer Stem Cellsmentioning
confidence: 96%
“…Several studies have suggested that patients taking MET for the treatment of diabetes also have a decreased incidence of pancreatic cancer [24,25]. MET has also been implicated in its ability to increase sensitivity of pancreatic cancer cells to GEM [24]. Other studies have concluded, however, that there is no association between MET use and cancer risk or prognosis [26,27].…”
Section: Introductionmentioning
confidence: 93%
“…MET is the primary drug used for the treatment of type 2 diabetes mellitus, and has become a drug of interest for the treatment of pancreatic cancer [19][20][21][22][23]. Several studies have suggested that patients taking MET for the treatment of diabetes also have a decreased incidence of pancreatic cancer [24,25]. MET has also been implicated in its ability to increase sensitivity of pancreatic cancer cells to GEM [24].…”
Section: Introductionmentioning
confidence: 99%
“…It enhanced the effect of denosumab, an antibody against RANKL (receptor activator of NFÎșB ligand, a cytokine), in inhibiting breast CSC spheroids [98]. It enhanced the sensitivity of pancreatic CSCs to gemcitabine in vivo, significantly reducing the tumor volume in murine xenografts [99]. When given in combination, metformin and doxorubicin showed the advantage of targeting both breast CSCs and non-stem cancer cells, by reducing the overall tumor growth and tumor remission in nude mice [100].…”
Section: Metforminmentioning
confidence: 99%